Pengaruh Likuiditas, Solvabilitas dan Intensitas Modal terhadap Financial Distress dengan Profitabilitas Sebagai Pemoderasi pada Sektor Transportasi - Annisa Sakinah Jaya; Basuki Toto Rahmanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine the effect of liquidity, solvency and capital intensity on financial distress with profitability as moderating. Liquidity was measured using the current ratio, solvency was measured using the debt equity ratio, capital intensity was measured using the capital intensity ratio, and financial distress was measured using the Altman Z-score method. The population uses transportation sector companies listed on the IDX in 2016-2020. The technique used in determining the sample is purposive sampling with a total of 155 observational data on transportation sector companies. The analytical technique used in this research is Moderate Regression Analysis (MRA). The hypothesis is accepted if the probability value is 0.05. The results show that: (1) Liquidity has a positive effect on financial distress, (2) Solvency has a negative effect on financial distress, (3) Capital intensity has a negative effect on financial distress, (4) Profitability weakens the influence of liquidity on financial distress, (5) Profitability weakens the effect of solvency on financial distress, (6) Profitability does not moderate the effect of capital intensity on financial distress.